fragmentation of knowledge processes and institutional knowledge: The Case of the Argentine Research and Teaching (1989-2003) - Saguier, Eduardo R. (Education Policy Analysis Archives, 2004)
The study of the centralizing mechanisms of academic power that very often work to obstruct and boycott individual and collective demands to produce critical knowledge, as well as impose circuits or networks made of multiple and combined knots (clientelism, nepotism, careerism and ethnocentric, sectarian and nepotic reciprocities), must necessarily go to their historical origins, analyzing several phenomena such as the coloniality of power, the subordination to a geopolitical and socio-technological stratification of knowledge, the fragmentation of knowledge processes, and other phenomena like endogamy, sectarianism, corruption and social, economic and political crises. Also, we are going to study the centripetal forces of decentralization, privatization or education federalism and their academic demands, the role of confidentiality in the formation of networks in academic and scientific environments, as well as their noxious effects in the practice of academic freedoms, the dissociations of power from knowledge and research from teaching, the distinction of teaching decentralization from research decentralization, the segregated education circuits, the intensity of the market of human capital and the quality of the levels of excellence of social and cultural capital, in the knowledge society. Also, we are going to refer to deformations in philanthropic politics and subsidies to scientific research, to models of technological innovation, the origin and development of the triadic partition of academic power or the tri-functional academic model, and the evaluation functions such as accreditation, extension, transference, counseling, programming and planning.